Integrated livestock management using participatory methodology: The example of livestock farmer field schools - Minjauw, B.; Romney, Dannie L. (EUCA-ICPTV, 2002)
Farmer field schools (FFS) are based on an innovative, participatory and interactive learning approach. The FFS approach was developed by FAO in South East Asia as a way for small-scale rice farmers to investigate and learn for themselves the skills required for, and the benefits to be obtained from adopting integrated pest management (IPM) practices in their paddy fields. This paper summarises the aim of the FFS; its first activities; grant per school; current FFS projects and their purpose and approach. The paper then looks into the agro-ecological system analysis (AESa), a methodology designed to improve observation skills and to develop decision making skills through analysis of a field situation. The paper ends with a brief description of the participatory technology Development (PTD), a process of collective and collaborative inquiry using comparative studies with the purpose of initiating community action on solving local problems.